Neurotoxicity as a major problem in childhood hematology - Mirzayeva Dilnozа Farkhadovna (The Bioscan, 2025)
The study examined the frequency of neurological complications in children with acute leukemia caused by chemotherapy. Among the patients, the majority had neurological manifestations related to the treatment. The most common complication was vincristine-induced polyneuropathy. Leukencephalopathy associated with methotrexate was also frequently observed, manifesting as seizures and stroke-like symptoms. These complications most often occurred at certain stages of treatment, which underscores the need for careful monitoring and adjustment of therapy to minimize negative outcomes.